Bilevel alternating direction iteration trajectory optimization for hypersonic morphing vehicles - Xu, Ziqi; Cheng, Lin; Gong, Shengping (Aerospace science and technology, 2025)
A bilevel iterative mixed-integer optimal control problem (MIOCP) algorithm based on the alternating direction method and sequential convex optimization is developed to solve the trajectory optimization problem of hypersonic morphing vehicles with discrete morphing modes. The algorithm introduces continuous relaxation variables to approximate the discrete control variables in MIOCP, decoupling them from the optimization objectives and dynamics of the original problem. It can be proven that the derived auxiliary problem provides a partial optimality to the initial problem. In the outer loop of the algorithm, discrete and continuous controls are alternately updated, avoiding the coupled solving of large-scale discrete and continuous variables. In the inner loop, the sequential convex optimization method utilizes linearization and discretization techniques to construct and solve a series of subproblems, addressing the continuous optimal control problem with fixed discrete variables. Simulations demonstrate the effectiveness and robustness of the algorithm, as well as its advantage in runtime performance. •A bilevel alternating iterative trajectory planning algorithm is proposed for hypersonic morphing vehicles.•The partial optimality of the proposed algorithm is theoretically established.•Numerical simulations are conducted to verify and discuss the effectiveness of the trajectory planning method.